Effect of dentin pretreatment on shear bond strength of three resin-based luting cements - Nihal Berke Bulut; Gülümser Evlioğlu; Bilge Gökçen Röhlig; Tamer Çelakıl (Istanbul University, 2018)
Purpose The aims of this study were; to compare the shear bond strength values of resin-based luting cements using etch-and-rinse, self-etching or self-adhesive techniques and to evaluate the effects of pretreatment with 0.2%, and 2% chlorhexidine (CHX) solutions on the bonding stability to dentin. Materials and methods Ninety specimens were divided into 9 groups of equal sample size (0.2% CHX, 2% CHX and no CHX application groups). Variolink N (multi-step etch-and-rinse technique), Panavia F2.0 (self-etching technique), or RelyX U200 (self-adhesive technique) resin-based luting cement was applied. All specimens were subjected to shear bond strength test (SBS) after bonding procedure. The mode of failure was analyzed by using a stereomicroscope. Results There were no significant differences among study groups for the dentin treatment factor. However, for luting cement factor, significant differences were found and Variolink N showed the highest SBS values. Conclusion CHX application has no immediate effect on the SBS values of any resin cements. Despite the development of simplified cementation techniques, etch-and-rinse technique is still the most reliable technique because of its high bond strength to dentin.